An FPTAS for the parallel two-stage flowshop problem - Dong, Jianming; Tong, Weitian; Luo, Taibo; Wang, Xueshi; Hu, Jueliang; Xu, Yinfeng; Lin, Guohui (Theoretical computer science, 2017)
We consider the NP-hard m-parallel two-stage flowshop problem, abbreviated as the (m,2)-PFS problem, where we need to schedule n jobs to m parallel identical two-stage flowshops in order to minimize the makespan, i.e. the maximum completion time of all the jobs on the m flowshops. The (m,2)-PFS problem can be decomposed into two subproblems: to assign the n jobs to the m parallel flowshops, and for each flowshop to schedule the jobs assigned to the flowshop. We first present a pseudo-polynomial time dynamic programming algorithm to solve the (m,2)-PFS problem optimally, for any fixed m, based on an earlier idea for solving the (2,2)-PFS problem. Using the dynamic programming algorithm as a subroutine, we design a fully polynomial-time approximation scheme (FPTAS) for the (m,2)-PFS problem.